(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Dhabas and multicuisine restaurant play an important role in food business. Preferences of travelers keeps on changing as per their requirements. Objective: Dhabas and multicuisine restaurants play an important role in food business. Preferences of travellers keeps on changing as per their requirement. The present study was done to identify the factor responsible for food tourism and secondly to identify the factors responsible for choosing the particular food outlet. Methodology: The data for the descriptive research was gathered from people (310) from all over India. A structured questionnaire with closed ended questions was prepared for survey and distributed to respondents through digital platform by Google Forms and also through offline mode. Data collection was done in the month of March-June, 2023. Result: The results revealed many important points for food travellers. Most (52%) of the travellers loved to dine at Dhaba. People loved to explore new cuisine. People who travels were emotionally attached with the local food. Further factors responsible for choosing food outlet were unique selling techniques, convenient vehicle parking, variation in food and beverage and maintaining cuisine authenticity. Cronbach’s alpha value calculated was found to be 0.0641 which is good and acceptable for the research. Conclusion: Thus study concludes to suggest that people loves to travel and want to enjoy different flavour of food. Extensive study can be done on any one of the two objectives achieved in the study.